Gold-FISH: A new approach for the in situ detection of single microbial cells combining fluorescence and scanning electron microscopy - Schmidt, Hannes; Eickhorst, Thilo; Mußmann, Marc (Systematic and applied microbiology, 2012)
A novel fluorescence in situ hybridisation (FISH) method is presented that allows the combination of epifluorescence and scanning electron microscopy (SEM) to identify single microbial cells. First, the rRNA of whole cells is hybridised with horseradish peroxidase-labelled oligonucleotide probes and this is followed by catalysed reporter deposition (CARD) of biotinylated tyramides. This facilitates an amplification of binding sites for streptavidin conjugates covalently labelled with both fluorophores and nanogold particles. The deposition of Alexa Fluor 488 fluoro-nanogold–streptavidin conjugates was confirmed via epifluorescence microscopy and cells could be quantified in a similar way to standard CARD–FISH approaches. To detect cells by SEM, an autometallographic enhancement of the nanogold particles was essential, and allowed the in situ localisation of the target organisms at resolutions beyond light microscopy. Energy dispersive X-ray spectroscopy (EDS) was used to verify the effects of CARD and autometallography on gold deposition in target cells. The gold-FISH protocol was developed and optimised using pure cultures and environmental samples, such as rice roots and marine sediments. The combination of epifluorescence and scanning electron microscopy provides a promising tool for investigating microorganisms at levels of high resolution. Correlative characterisation of physicochemical properties by EDS will allow for the analysis of microbe-surface interactions.